Larvicidal effects of various Euro-Asiatic plants against Culex quinquefasciatus Say larvae (Diptera: Culicidae) - Pavela, Roman (Parasitology research, 2008)
Extracts from 56 species of plants in the Euro-Asiatic region were tested for larvicidal activity against the fourth larval instar of the mosquito Culex quinquefasciatus Say (Diptera: Culicidae). All plant extracts showed larvicidal activity after 24 h of exposure to the plant extracts in a maximal dose of 500 ppm. The extracts of the plants Otanthus maritimus and Ammi visnaga displayed the highest larvicidal effect (LD(50) 7 and 9 ppm, respectively) followed by Acer pseudoplatanus, Humulus japonicus, Acer platanoides, Satureja hortensis, Ocimum basilicum and Thymus vulgaris (LD(50) 23, 25, 28, 28, 32 and 48 ppm respectively). For eight species, the appraisal value of LD(50) was between 51 and 100 ppm, another eight species from 101 to 200 ppm, 15 species from 201 to 500 ppm and for 17 species, low mortality showed no lethal dose (LD(50)>500 ppm).
Keywords: Lethal Dose 50; Plants, Medicinal; insekticidy; Asia; Insecticides; Larva; Plant Extracts; LD50; Animals; Asie; léčivé rostliny; zvířata; Evropa; rostlinné extrakty; Culex; Europe; larva